Chinese Creator Economies : Labor and Bilateral Creative Workers. - Lin, Jian (New York University Press, 2023)
The paradoxical relationship between Chinese creative workers and the stateChinese Creator Economies dives into the paradoxical lives lived by creative professionals in emerging economies across China. Jian Lin contextualizes the socioeconomic conditions in which cultural production takes place and pushes back against the dominant understanding of Chinese media as a centralized, state-controlled apparatus by looking at how individual creative workers grapple with governance and precarity in the Chinese cultural industries and develop their bilateral subjectivities within the politico-economic system of Chinese media. Drawing on intensive empirical research conducted on creative labor practices across television, journalism, design, and social media, Chinese Creative Economies looks at both Chinese and foreign-born content creators, exploring the tensions between Beijing's limits on individual creativity, and its aspirations to become a global hub for cultural production. Lin maintains that it is the production of bilateral creatives that generates and maintains hope for the future of those who live and work within the cultural economies of China.
Description based upon print version of record.
Keywords: Cultural industries -- China -- Employees.; Arts -- China.; China -- Cultural policy.; Industries culturelles -- Chine -- Personnel.; Arts -- Chine.; SOCIAL SCIENCE / Media Studies.; Arts; Cultural policy; China; Media studies.; Labour economics.; Industry & industrial studies.; Media, entertainment, information & communication industries.; Industry.; Electronic books.